Optimizing distribution system performance: A comprehensive review of power loss minimization techniques - Moufid, Ismail; En-nay, Zineb; Naciri, Soukaina; El Markhi, Hassane (Institute of Advanced Engineering and Science, 2025)
This article presents a thorough examination of contemporary techniques aimed at minimizing losses in distribution networks by strategically allocating capacitors, distributed generators (DG), and distribution static synchronous compensators (DSTATCOM). Through an extensive review of background literature and the analysis of current methodologies, the study distills insights from research articles spanning four decades. The survey encompasses diverse single and multi-objective methods, considering various constraints in addressing the distribution system loss minimization problem. Key findings emphasize the effectiveness of capacitor allocation in high voltage distribution networks, the efficiency of DG allocation in integrating small-scale generation, and the growing interest in DSTATCOM allocation for its advantages over traditional capacitor allocation. Particular attention is given to simultaneous techniques, identified as the most efficient approach for enhancing overall system performance.